Association Between Power Limb Muscles And Speed Running To Accuracy of Shooting Ball to Goal of primary school students at Gawanan, Karanganyar 2015 - Mustakim, Subangun; , Umi Budi Rahayu, S.Fis, M.Kes; , Dwi Rosella Komalasari, S.Fis, M.Fis, Dipl (2016)
Background: Football is the most popular sport in the world. Kicking the ball to goal can do if a football player have limb muscles good, and running fast so, it expected to create a goal. The results of pre study to 25 students in kick practice to goal, 16 students missing kick. The objectives of Research: To know association between power limb muscles and speed running to accuracy of shooting ball to goal of primary school students of Gawanan Karanganyar. The Benefit of Research: Expected in this research can increase knowledge and repertoire of football in particular ways and techniques in a football game. The Method of Resarch: The kind of Research is quantitative, and crossectional approach. Sample are 50 male students of 4.5, and 6 class. Taking Sample use porpusive sampling technique. data collected by measures power limb muscles with jump test. Speed run use measure time from sprint of 30 meters. The accuracy shooting with 10 times from 12 metres disctance. Data analysis use correlation pearson product moment and linear regression multiple test. Result of the Research: Results that association between power limb muscles with accuration shooting ball to goal with p = 0,001. Association between speed running 30 meters with accuration shooting ball to goal with p = 0,001. linear regression multiple test with equation Y= 82,710 + 0,632X1 -7,873X2. From simultant test with Ftest= 35,574; Ftable = 3,32 and p = 0,001 Conclusion: There was a association between power limb muscles and speed running to accuracy of shooting ball to goal of primary school students of gawanan karanganyar Keyword : Power Limb Muscles, Speed Running, Accuracy of Shooting, Football, Students